2017
DOI: 10.5424/sjar/2017152-10548
|View full text |Cite
|
Sign up to set email alerts
|

Global Malmquist indices of productivity change in Egyptian wheat production

Abstract: This study aims to measure the total factor productivity of the main governorates of wheat production in Egypt during the time period 1990-2012 and decompose it into technical change, efficiency change and scale change. We used Global Malmquist TFP index as a non-parametric approach. The results indicated that the contribution of technical change component is more important than the efficiency change component. In fact technical change rose, 25.7%, while efficiency change presented a little decline, 3.7%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…and Alarcon, S. (2017) mainly focused on measuring the TFP of major wheat-producing provinces in Egypt from 1990 to 2012, and decomposed it into technological change, efficiency change, and scale change. They found that the contribution of technological change components is more important than that of efficiency change components [29]. Njuki, E. et al (2018) focused on quantifying and investigating the role of changing weather patterns in explaining annual fluctuations in the TFPG [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…and Alarcon, S. (2017) mainly focused on measuring the TFP of major wheat-producing provinces in Egypt from 1990 to 2012, and decomposed it into technological change, efficiency change, and scale change. They found that the contribution of technological change components is more important than that of efficiency change components [29]. Njuki, E. et al (2018) focused on quantifying and investigating the role of changing weather patterns in explaining annual fluctuations in the TFPG [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technical change rose, 25.7%, while efficiency change presented a little decline, 3.7%. The decomposition of efficiency change indicated that the main problem of wheat production in Egypt was scale efficiency that worsened by 5.5% [10].…”
Section: Ebatamentioning
confidence: 99%